Prevalence and extent of partial edentulism and its association with demographic variables- an epidemiological survey - AGARWAL, SANJOG; AHMED, NABEEL; MAITI, SUBHABRATA (The journal of contemporary issues in business and government, 2021)
Advances in preventive dentistry are not unknown to mankind despite that , edentulism is a major public health issue worldwide. Edentulism has been hallmarked as “final marker of disease burden for oral health.” The objective of the present study is to determine the relationship between socio-demographic variables and partial edentulism. A Cross-sectional, descriptive study was conducted in an institution, on randomly selected individuals. The study group consisted of adult patients who attended the outpatient Department of Prosthodontics from June 2019- March 2020.Data collection was done by using college database and Chi-square test and frequency analysis was used to explore the relationship between two variables Males had more missing teeth in general compared to females.Males had more missing teeth in upper anterior region than females.Females had more missing teeth in upper posterior region.Males had more missing teeth in lower anterior region compared to females.Females had more missing teeth in lower posterior region.Age group(31-40) years had more missing teeth over all. Upper anteriors were more missing in Age group(31-40) years.Upper posteriors were more missing in Age group(31-40) years.Lower anteriors were more missing in Age group(31-40) years.Lower posterior were more missing in Age group(31-40) years.In general anterior teeth were more missing in males compared to posterior teeth which were more missing in females.Age group(31-40) years is more prone to missing teeth in partial edentulous cases. There was an increase in the number of missing teeth as the age advances.More awareness is needed among the population in order to maintain good oral hygiene.